The phenomenon of autohagiography: On the question of the replacement of subjectivity in Christian mysticism - M. Yu. Reutin (Шаги, 2023)
The article attempts to comprehend the phenomenon of religious consciousness. The aim is to describe, as an immanent experience, psychotechnics (work on oneself) — that which understands itself and describes itself in its own language with the help of metaphysical concepts. The introduction considers the so-called “Eulogy” of Moscow priest Alexei Mechev, previously analyzed by P. A. Florensky and V. N. Toporov. What is incomprehensible and intriguing about the “Eulogy” is that it is composed to himself and by himself in the most commendable way (and by no means in a humble tone, as one would expect) and essentially is a glorification of oneself as a saint. In parts I and II of the article, the same phenomenon is examined on the basis of works of 14thcentury German mystics: the autobiography “Vita” by the Constance mystic Heinrich Suso (1295/1297–1366) and the diary notes of the Zurich visionary Elsbeth von Oye (d. 1341/1342), which have survived in the original. In both the first and the second case, attention is paid to the phenomenon of double voicing, when statements endowed with performative power and devoid of any doubt about their complete, unconditional rightness are adjacent to the most derogatory and humble self-assessments. This is what the replacement of subjectivity looks like: as the human subjectivity of the charismatic is eliminated, the subjectivity of God, the divine “spark” unfolds in him: the emanation of God that is in him, which. however, is of another nature than the charismatic, in relation to which the charismatic himself acts as an instrument. Setting itself no limits, the imperative and categorical discovery of a “spark” in a humble charismatic corresponds to the glorification of oneself in Father A. Mechev’s “Eulogy”, which is emphasized in the Conclusion and explicated in several findings.